Experimental buckling performance of eucalyptus-based oriented oblique laminated strand lumber columns under centric and eccentric compression. (30th November 2020) - Chen, Jiawei; Xiong, Haibei; Wang, Zhifang; Yang, Linqing
Highlights: A novel eucalyptus-based oriented oblique strand lumber (ESWood) was proposed. Considering various eccentricities, the buckling performance of intermediate ESWood columns was presented. A calculation approach for predicting the inelastic buckling load of intermediate ESWood columns was introduced. Abstract: Engineered wood-based products manufactured from fast-growing wood species have gained increasing attraction as the demand for using wood in building constructions continues to grow. An innovative oriented oblique strand laminated lumber called Eucalyptus Strand Wood (ESWood) made from fast-growing eucalyptus is presented in this paper. A series of material tests using small clear specimens were carried out to study the basic mechanical properties of the ESWood, while experiments on full-scale columns were conducted to study the buckling behavior of intermediate ESWood columns under centric and eccentric compression. The failure modes and load-carrying capacity of the columns with various eccentricities were reported and evaluated. Efforts were also made to provide a preliminary calculation approach for predicting the critical buckling load of intermediate ESWood columns under both centric and eccentric compression. Based on the analyses presented in this paper, it appears that the oblique strand lamination of ESWood results in great compactness and strength. Compared with the engineered Spruce-pine-fir, wood scrimber, and Glubam, the ESWood has comparable strength to serve as a construction and building material, especially as structural columns. For intermediate ESWood columns under centric and eccentric compression, buckling was observed as the primary failure mode. As the eccentricity increased, the critical buckling load decreased gradually with increasing critical deflection. To predict the inelastic buckling load, Newlin's formula with either the Newlin-Gahagan approach or Yoshihara approach was adopted. The influence of the yielding stress and critical buckling stress estimation was discussed, and the results show that Newlin's formula with Yoshihara approach provides good predictions for the critical load of ESWood intermediate columns. The presented test results and analyses provide basic knowledge for supporting more applications of such fast-growing eucalyptus-based material in building constructions.